2006
DOI: 10.1074/jbc.m601537200
|View full text |Cite
|
Sign up to set email alerts
|

Murine Leukemia Virus Regulates Alternative Splicing through Sequences Upstream of the 5· Splice Site

Abstract: Alternative splicing of the primary transcript plays a key role in retroviral gene expression. In contrast to all known mechanisms that mediate alternative splicing in retroviruses, we found that in murine leukemia virus, distinct elements located upstream of the 5 splice site either inhibited or activated splicing of the genomic RNA. Detailed analysis of the first untranslated exon showed that the primer binding site (PBS) activates splicing, whereas flanking sequences either downstream or upstream of the PBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Previous studies have demonstrated that modulation of the viral 5= leader sequence affects the cytoplasmic accumulation of spliced and unspliced MLV transcripts. For instance, deletion of the first 28 nt of the R region is critical for the cytoplasmic level of unspliced full-length viral transcripts (20,64), while deletions in the PBS sequence also modulate the balance between unspliced and spliced MLV transcripts (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that modulation of the viral 5= leader sequence affects the cytoplasmic accumulation of spliced and unspliced MLV transcripts. For instance, deletion of the first 28 nt of the R region is critical for the cytoplasmic level of unspliced full-length viral transcripts (20,64), while deletions in the PBS sequence also modulate the balance between unspliced and spliced MLV transcripts (21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the importance of the 5= UTR for the alternative splicing of MLV transcripts; the PBS activates splicing, while flanking sequences downstream of the PBS (3= PBS) are inhibitory (21). We generated the MLV splicing mutants pAMS⌬PBS and pAMS⌬3=PBS based on the pAMS plasmid (Fig.…”
Section: Fig 4 Mapping Analysis Of the 70-nt Cae (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Gammaretroviral vectors termed SF91 were derived from SF91.GFP (11,31). The vector SF91aPBS.GFP.pre was generated by introducing the artificial primer binding site (aPBS) as an XbaI/ApaI fragment from SF91aPBS.GFP (8,15) in SF91.GFP.pre (31). The retroviral vector used for engineering human Cre reporter cells to express Fv1 n was derived from pCFCR (21).…”
Section: Methodsmentioning
confidence: 99%
“…17,18 This has been associated to an abundant transcription from the internal promoter driving transgene expression, which may occur at the expense of full-length viral RNA transcription originating from the LTR in packaging cells. 18,19 Various approaches were taken to overcome these limitations, such as the introduction of the post-transcriptional element from Woodchuck hepatitis virus into the 3¢-untranslated region of SIN vectors, 20,17 or the incorporation of upstream polyadenylation enhancer elements derived from viral or cellular genes into the 3¢U3 region of the LTR, allowing partial recovery of high viral vector titers. 21 Recently, it has been observed that the use of a strong internal enhancer/promoter in SIN vectors may increase transgene expression but that this may also increase host cell transformation.…”
Section: Retroviral Vectors Represent An Important Tool In Human Genementioning
confidence: 99%